Establishing optimal selenium status: results of a randomized, double-blind, placebo-controlled trial - Hurst, Rachel; Armah, Charlotte N; Dainty, Jack R; Hart, Dave J; Teucher, Birgit; Goldson, Andrew J; Broadley, Martin R; Motley, Amy K; Fairweather-Tait, Susan J (The American journal of clinical nutrition, 2010)
BACKGROUND: Dietary recommendations for selenium differ between countries, mainly because of uncertainties over the definition of optimal selenium status. OBJECTIVE: The objective was to examine the dose-response relations for different forms of selenium. DESIGN: A randomized, double-blind, placebo-controlled dietary intervention was carried out in 119 healthy men and women aged 50-64 y living in the United Kingdom. Daily placebo or selenium-enriched yeast tablets containing 50, 100, or 200 μg Se ([almost equal to]60% selenomethionine), selenium-enriched onion meals ([almost equal to]66% γ-glutamyl-methylselenocysteine, providing the equivalent of 50 μg Se/d), or unenriched onion meals were consumed for 12 wk. Changes in platelet glutathione peroxidase activity and in plasma selenium and selenoprotein P concentrations were measured. RESULTS: The mean baseline plasma selenium concentration for all subjects was 95.7 ± 11.5 ng/mL, which increased significantly by 10 wk to steady state concentrations of 118.3 ± 13.1, 152.0 ± 24.3, and 177.4 ± 26.3 ng/mL in those who consumed 50, 100, or 200 μg Se-yeast/d, respectively. Platelet glutathione peroxidase activity did not change significantly in response to either dose or form of selenium. Selenoprotein P increased significantly in all selenium intervention groups from an overall baseline mean of 4.99 ± 0.80 μg/mL to 6.17 ± 0.85, 6.73 ± 1.01, 6.59 ± 0.64, and 5.72 ± 0.75 μg/mL in those who consumed 50, 100, or 200 μg Se-yeast/d and 50 μg Se-enriched onions/d, respectively. CONCLUSIONS: Plasma selenoprotein P is a useful biomarker of status in populations with relatively low selenium intakes because it responds to different dietary forms of selenium. To optimize the plasma selenoprotein P concentration in this study, 50 μg Se/d was required in addition to the habitual intake of [almost equal to]55 μg/d. In the context of established relations between plasma selenium and risk of cancer and mortality, and recognizing the important functions of selenoprotein P, these results provide important evidence for deriving estimated average requirements for selenium in adults. This trial was registered at clinicaltrials.gov as NCT00279812.